High efficiency RF power amplifier with closed loop system for public safety radio communications / Lokesh Anand Vijayakumaran - Lokesh Anand, Vijayakumaran (2019)
The design of transmitter line up for public safety radio communications entails many challenges at both architecture and circuit levels. The key point in this research work concerns the development of RF PA line up where the research introduces 3 design methodologies which is not available in current conventional 2 -way radio design. Firstly, a parallel-combined impedance matching technique is introduced where it enables the designers to develop broadband PA with actual PA device impedance. Since developing a RF PA line up alone is not enough, and a fast output power ramp up is needed for a quick data transmission during mission critical operation. So a new technique to characterize the behavioural response of multistage RF PA is explored. For that, a simplified design methodology of closed loop PA with DC current sensing of multistage PA (cascaded) and voltage shaping algorithm is used in this work. The above two methodologies are combined and a novel closed-loop adaptive power amplifier (PA) design which provides constant efficiency across wide power level is developed (state of art of current work). Experimental results demonstrated output power of ~80 W and gain of 42 dB over the bandwidth of interest. Constant efficiency (48%) and transient timing response of 1.1 ms is achieved while maintaining good transient power of less than -50 dB over the frequency range of 400 to 520 MHz. This work allows the public safety and mission critical two-way radio products been accepted widely since the users have the platform for building interoperability into their systems. Since transmitting is the most energy intensive operation, the adaptive RF PA design can typically function 40% longer in terms of battery life than the non-adaptive c